(untitled) (SAARC Journal of Agriculture, 2018)
Marek’s disease (MD) is a lymph proliferative disease of chickens, characterized by progressive emaciation, morbidity and mortality. The causative agent is a cell associated oncogenic alpha-herpes virus. This study investigated an outbreak of MD in a pullet farm (N=2200) of Ramu Upazilla, Cox’s bazaar during May 2016 vaccinated against MD. The infectivity was reported on day 45 of age. Birds (N=10) submitted to diagnose disease at necropsy in the Department of Pathology, Bangladesh Agricultural University showed prominent keel bone, asymmetric progressive paralysis of one or both of the legs and wings. At necropsy, the skeletal muscle appeared thinner and there was enlargement of liver, spleen, kidney and sciatic nerve. Impression smears prepared from the liver showed huge infiltration of lymphocytes. Sections of heart, lungs, liver, kidney, nerve, skin and spleen were stained with hematoxylin and eosin showed wide spread infiltrations and accumulation of lymphocytes. Lymphocytic infiltration was seen in the skin, nerves and all visceral organs and showed combined infectivity due to visceral and classical forms. The etiology of MD was confirmed by using polymerase chain reaction (PCR) targeting fragment of Meq gene of very virulent plus or very virulent MDV1. Results of PCR showed amplification of 317bp fragment of Meq gene suggestive for infectivity due to MDV1GA (Md/5) strain. It requires isolating viruses in culture to test further for its virulence and pathotype in vivo. Sequencing and phylogenetic analysis of Meq gene may unveil the pathotype of the virus involved. SAARC J. Agri., 16(1): 181-192 (2018)